An Analysis Upon Various Outcomes on Achievement Concept of High/Low Achievers: a Case Study of Secondary Schools In India: Exploring the relationship between achievement concept and outcomes in high/low achievers in Indian secondary schools (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The present study was carried out to investigate. A Studyof Achievement Motivation of High School Students with relation to high and lowachiever students. The study was conducted in selected sample by random methodon 30 boy and 30 girls students' data. For investigation, students securing upto 50 percent marks were considered as lower achiever and those secured morethan 85 percent marks were considered as lower achiever and those secured morethan 85 percent marks were considered as high achievers. This task carried onhigh school students. Their ranking is done on the basis of marks secured in9th class the year in examination. The Achievement Motivation inventory foranalysis was carried out by ' Achievement Motivation inventory'.  The high schoolstudents tend to bear the ability to think or imagine in a different way. Inthe present study the sum of fluency, flexibility and the originality in anindividual is creativity. The objectives of the study comprised to know thelevels of creativity, intelligence, achievement motivation, anxiety andself-concept of the high school students and to know the effect of theirintelligence, achievement motivation, anxiety, gender, self-concept, and areaon creativity.